PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE UNTUK MENINGKATKAN KEMAPUAN BERPIKIR LOGIS DAN PRESTASI BELAJAR - Sarmidi Sarmidi (DIADIK, 2020)
This study aims (1) to describe the application of the Picture and Picture model to improve the logical thinking skills of fifth graders at SDN Gugus 2 Kikim Timur, (2) to describe the application of the Picture and Picture model to improve the learning achievement of fifth graders at SDN Gugus 2 Kikim Timur, and (3) To describe the effectiveness of the application of the Picture and Picture model in improving the learning achievement of fifth graders at SDN Gugus 2 Kikim Timur. This research method is a combination method between Classroom Action Research (CAR) and continued with Quasi Experiments. The research subjects for the CAR were fifth grade students who opened 21 people. For the quasi-experimental, all 34 students of class V SD Negeri Gugus 2 Kikim Timur totaled 34. The sample was taken using a pretest-posttest control design matching procedure, with purposive sampling technique, not by drawing lots but selected class V SD Negeri 20 Kikim Timur as many as 17 people as the experimental class, and class V SD Negeri 13 Kikim Timur as many as 17 people as the control class. Data on the application of the picture and picture type cooperative learning model and logistical thinking skills were collected using observation techniques, while student achievement data was collected using tests. The results of the t-test on the quasi-experimental post-test between the experimental class and the control class obtained a t-count of 8.377. It can be said that the effective application of the picture and picture type of cooperative learning model can improve the ability to think and learn Indonesian in the fifth grade of SD Negeri Gugus 2 Kikim Timur